IL-17A reprograms intestinal epithelial cells to facilitate HIV-1 replication and outgrowth in CD4+ T cells - Tomas Raul Wiche Salinas (Elsevier, 2021)
Summary: The crosstalk between intestinal epithelial cells (IECs) and Th17-polarized CD4+ T cells is critical for mucosal homeostasis, with HIV-1 causing significant alterations in people living with HIV (PLWH) despite antiretroviral therapy (ART). In a model of IEC and T cell co-cultures, we investigated the effects of IL-17A, the Th17 hallmark cytokine, on IEC ability to promote de novo HIV infection and viral reservoir reactivation. Our results demonstrate that IL-17A acts in synergy with TNF to boost IEC production of CCL20, a Th17-attractant chemokine, and promote HIV trans-infection of CD4+ T cells and viral outgrowth from reservoir cells of ART-treated PLWH. Importantly, the Illumina RNA-sequencing revealed an IL-17A-mediated pro-inflammatory and pro-viral molecular signature, including a decreased expression of type I interferon (IFN-I)-induced HIV restriction factors. These findings point to the deleterious features of IL-17A and raise awareness for caution when designing therapies aimed at restoring the paucity of mucosal Th17 cells in ART-treated PLWH.